Subcutaneous Sarcoidosis during Pegylated Interferon Alfa and Ribavirin Treatment for Chronic Hepatitis C - R. Rodríguez-Lojo; M. Almagro; J. M. Barja; F. Piñeyro; L. Pérez-Varela; J. Del Pozo; M. T. Yebra-Pimentel; E. Fonseca (Dermatology Research and Practice)
Interferon is used to treat hepatitis C virus infection and its cutaneous side effects are well known. Recently, interferon-induced sarcoidosis has been reported. We report a new case of sarcoidosis during pegylated interferon alfa and ribavirin treatment with an unusual presentation in a woman with previous episodes of erythema nodusum and nodular vasculitis related to HCV.